Structural characterizations and electrochemical performances of rGO-based anode materials for lithium-ion battery - Mohd Abid, Mohd Asyadi Azam; Safie, Nur Ezyanie; Chun, Khean Chiew; Abdul Aziz, Mohd Fareezuan; Md Sairi, Mohamad Nazmi Faiz; Takasaki, Akito (Springer, 2023)
Lithium-ion bateries (LIBs) in the current market are becoming insufcient to meet the increasing demand for portable electronic devices and large-scale applications due to the low theoretical capacity (372 mAh/g) and poor rate performance of the graphite anode. This work focuses on electrochemical performance analysis using graphene as an active material in constructing an anode for LIB. mGraphene has been used in the form of reduced graphene oxide (rGO) because it can be produced using more scalable and cost-efective techniques. Three graphene samples were tested, including synthesized rGO, industrial graphene, and commercial rGO. Raman spectroscopy confrms the successful reduction of rGO by chemical synthesis and shows that the commercial rGO has the fewest defects among the three graphene samples. XRD characterization shows that chemically synthesized rGO has a more crystallized structure and larger d-spacing; Meanwhile, electrochemical analysis showed that the commercial rGO performs better, including cyclic stability. The frst discharge capacity is 2383 mAh/g with a high current density of 100 mA/g. The commercial rGO delivers an energy density of up to 1866 Wh/kg, demonstrating the potential to produce compact, high energy density bateries for electronic devices, electric cars and power grid storage applications.